The effect of ultrafiltration on end-cardiopulmonary bypass hematocrit during cardiac surgery. (July 2018) - Mongero, Linda; Stammers, Alfred; Tesdahl, Eric; Stasko, Andrew; Weinstein, Samuel
Objective: Ultrafiltration (UF) during cardiopulmonary bypass (CPB) is a well-accepted method for hemoconcentration to reduce excess fluid and increase hematocrit, platelet count and plasma constituents. The efficacy of this technique may confer specific benefit to certain patients presenting with acquired cardiac defects. The purpose of this study was to retrospectively evaluate the effect of UF on end-CPB hematocrit by cardiac surgical procedure type. Methods: A review of 73, 506 cardiac procedures from a national registry (SCOPE) was conducted between April 2012 and October 2016 at 197 institutions. Cases included in this analysis were those completed without intraoperative red blood cell transfusion and where zero-balance UF was not used. The primary end point was the last hematocrit reading taken before the end of CPB, with a secondary end point of urine output during CPB. In order to isolate the effect of the UF volume removed, we controlled for a number of confounding factors, including: first hematocrit on CPB, total asanguineous volume, estimated circulating blood volume, CPB urine output, total volume of crystalloid cardioplegia, total volume of other asanguineous fluids administered by both perfusion and anesthesia, type of cardiac procedure, acuity, gender, age and total time on CPB. Descriptive statistics were calculated among five subgroups according to the UF volume removed: no volume removed and quartiles across the range of UF volume removed. The effect of UF volume on primary and secondary end points was modeled using ordinary least squares and restricted cubic splines in order to assess possible non-linearity in the effect of the UF volume while controlling for the above-named confounding factors. An interaction term was included in each model to account for possible differences by procedure type. Results: The study found a statistically significant non-linear pattern in the relationship between the UF volume removed and the last hematocrit on bypass (X 2 = 172.5, df=24, p<0.001). For most procedure types, UF was most effective at increasing the last hematocrit on CPB, from 1 mL to approximately 2.5 L, with continued improvements in hematocrit coming more slowly as the UF volume was increased above 2.5 L. There were statistically significant interactions between UF and procedure type (X 2 = 78.5, df=24, p<0.0001) as well as UF and starting hematocrit on CPB (X 2 = 234.0, df=4, p<0.0001). In a secondary end-point model, there was a statistically significant relationship between the ultrafiltration volume removed and urine output on bypass (X 2 = 598.9, df=28, p<0.001). Conclusion: The use of UF during CPB resulted in significant increases in end-hematocrit, with the greatest benefit shown when volumes were under 2.5 L. We saw a positive linear benefit up to 2.5 L removed and, thereafter, in most procedures, the benefit leveled off. However, of note is markedly decreased urine output on bypass as the ultrafiltration volumes increase.